Relationship between soil moisture content in paddy field and its image texture - Bejo, Siti Khairunniza; Sumgap, Nor Hafizah; Mohd Johari, Siti Nurul Afiah (Penerbit Universiti Teknologi Malaysia Press, 2016)
The aim of this study is to identify the relationship between soil moisture content and its image texture. Soil image was captured and converted into CIELUV color space. These images were later used to develop two dimensional gray level co-occurrence matrix. Eight texture features extracted from gray level co-occurrence matrix namely mean, variance, homogeneity, dissimilarity, entropy, contrast, second moment and correlation was used for the analysis. The results has shown that the image texture properties can be used to relate with soil moisture content, where variance, homogeneity, dissimilarity, entropy, contrast, second moment and correlation gave significant responds to the moisture content. The highest value of correlation was gathered from entropy with r = -0.522.